Regulation of plant immune receptors by ubiquitination - Furlan, Giulia; Klinkenberg, Jörn; Trujillo, Marco (Frontiers in Plant Science, 2012)
From pathogen perception and the activation of signal transduction cascades to the deployment of defense responses, protein ubiquitination plays a key role in the modulation of plant immunity. Ubiquitination is mediated by three enzymes, of which the E3 ubiquitin ligases, the substrate determinants, have been the major focus of attention. Accumulating evidence suggests that ubiquitination modulates signaling mediated by pattern recognition receptors (PRRs) and is important for the accumulation of nucleotide-binding leucine-rich repeat (NB-LRR) type intracellular immune sensors. Recent studies also indicate that ubiquitination directs vesicle trafficking, a function that has been clearly established for immune signaling in animals. In this mini review, we discuss these and other recent advances and highlight important open questions.